MENTAL HEALTH OF STUDENTS DURING INITIAL PERIOD OF THE WAR IN UKRAINE - Polyvianaia, Maryna; Pishel , Vitaliy (Collection of scientific papers «ΛΌГOΣ», 2023)
Due to the war in Ukraine which started on February 24, 2022, the problem of mental health has acquired special importance. The results of research in other countries have indicated a significant negative impact of war on the state of mental health of student youth, their high susceptibility to the development of post-traumatic mental disorders, depression, anxiety disorders and addiction to psychoactive substances [1-5]. Therefore, it is currently extremely relevant to determine the structure and clinical features of mental disorders among students, to provide them with psychological and psychiatric assistance as well as the development and implementation of a comprehensive model to protect the mental health of young people in war and post-war periods.